Phonemic Analysis of English Suprasegmental Features Produced by the Students of Kresna English Institute - Alfida Firdaus Fuiadatil Aziz; Ayu Fatmawati; Imam Baehaki (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2022)
Abstract Learning about pronunciation is also learning about stress and intonation. They are aspects of suprasegmental. This research is conducted for the students of English Comprehension Program at Kresna English Institute who have learned about pronunciation in speech. This research uses a qualitative approach with a case study design because this research describes a setting, an object, or a particular event in detail and depth. The results of this research are: there are still many errors made by English Comprehension program students, especially in the pronunciation program out of a total of 10 students there are many misplaced that vary in each student and also 4 out of 10 students give an increased intonation of some words in sentences or even no intonation made by students or in this case students use flat intonation, thus creating the wrong pattern of contour intonation; and 2) that factors are involved in the production of English suprasegmental features by the students, one of which is the mother tongue of each student who is different, researchers also found that the influencing factor is the awareness of the students in learning this comes from within each student, and researchers also find as the third factor, namely the surrounding environment of students who can form a habit in terms of socializing and communicating; and 3) the method carried out by the teacher seems to be able to improve the ability of students both in terms of pronouncing their word stress and in terms of intonation imitating videos and examples given by the teacher.